2021
DOI: 10.1097/md.0000000000023883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the therapeutic effect of acoustic therapy combined with acupuncture on idiopathic tinnitus

Abstract: Background: There is no effective treatment for idiopathic tinnitus. Both acoustic therapy and acupuncture have been used in the treatment of idiopathic tinnitus, but the clinical efficacy is quite different. For there is no clinical study combining the 2, the purpose of this randomized controlled trial is to evaluate the effectiveness and safety of acoustic therapy combined with acupuncture in the treatment of idiopathic tinnitus. Methods: This is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Acupuncture is recommended for the relief of chronic tinnitus in traditional Chinese medicine. Although some studies reported that acupuncture had few effective treatments for tinnitus (Podoshin et al, 1991;Kim et al, 2012), recent studies showed an effective acupuncture treatment for tinnitus (Pang et al, 2019;Huang et al, 2021;Wang et al, 2021). The acupoints commonly used are Tinggong (SI 19), Tinghui (GB 2), Yifeng (TE 17), Shuaigu (GB 8), Ermigen (R 2), Fengchi (GB 20), Zhongzhu (TE 3), Luxi (TE 19), and Ermen (TE 21).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is recommended for the relief of chronic tinnitus in traditional Chinese medicine. Although some studies reported that acupuncture had few effective treatments for tinnitus (Podoshin et al, 1991;Kim et al, 2012), recent studies showed an effective acupuncture treatment for tinnitus (Pang et al, 2019;Huang et al, 2021;Wang et al, 2021). The acupoints commonly used are Tinggong (SI 19), Tinghui (GB 2), Yifeng (TE 17), Shuaigu (GB 8), Ermigen (R 2), Fengchi (GB 20), Zhongzhu (TE 3), Luxi (TE 19), and Ermen (TE 21).…”
Section: Introductionmentioning
confidence: 99%